Governing the Ephemeral: Secondary Forest in Peru - Sears, R.R.; Guariguata, Manuel R.; Cronkleton, P.; Miranda Beas, C. (Center for International Forestry Research, 2021)
Secondary forest is an increasingly prevalent component of forest cover across the globe providing wildlife habitat, ecosystem services and valuable goods.